Pharmacokinetic Study of Adjuvant Gemcitabine Therapy for Biliary Tract Cancer following Major Hepatectomy (KHBO1101) - Fujiwara, Yutaka; Kobayashi, Shogo; Nagano, Hiroaki; Kanai, Masashi; Hatano, Etsuo; Toyoda, Masanori; Ajiki, Tetsuo; Takashima, Yuki; Yoshimura, Kenichi; Hamada, Akinobu; Minami, Hironobu; Ioka, Tatsuya (PloS one, 2015)
Biliary tract cancer (BTC) patients who have undergone surgical resection with major hepatectomy cannot tolerate the standard gemcitabine regimen (1,000 mg/m2 on days 1, 8, and 15 every 4 weeks) due to severe toxicities such as myelosuppression. Our dose-finding study of adjuvant gemcitabine therapy for biliary tract cancer following major hepatectomy determined that the recommended dose is 1,000 mg/m2 on days 1 and 15 every 4 weeks. Here, we evaluate the pharmacokinetics and pharmacodynamics of gemcitabine in these subjects. We evaluated BTC patients scheduled to undergo surgical resection with major hepatectomy followed by gemcitabine therapy. A pharmacokinetic evaluation of gemcitabine and its main metabolite, 2',2'-difluorodeoxyuridine (dFdU), was conducted at the initial administration of gemcitabine, which was given by intravenous infusion over 30 min at a dose of 800-1,000 mg/m2. Physical examination and adverse events were monitored for 12 weeks. Thirteen patients were enrolled from August 2011 to January 2013, with 12 ultimately completing the pharmacokinetic study. Eight patients had hilar cholangiocarcinoma, three had intrahepatic cholangiocarcinoma, and one had superficial spreading type cholangiocarcinoma. The median interval from surgery to first administration of gemcitabine was 65.5 days (range, 43-83 days). We observed the following toxicities: neutropenia (n = 11, 91.7%), leukopenia (n = 10, 83.3%), thrombocytopenia (n = 6, 50.0%), and infection (n = 5, 41.7%). Grade 3 or 4 neutropenia was observed in 25% (n = 3) of patients. There were differences in clearance of gemcitabine and dFdU between our subjects and the subjects who had not undergone hepatectomy. Major hepatectomy did not affect the pharmacokinetics of gemcitabine or dFdU. UMIN-CTR in (JPRN) UMIN000005109.